A Potentially Adjustable Modification of the Nishida Procedure. Issue 2 (3rd April 2023) - Tauscher, Robert; Haynie, Mathew; Pineles, Stacy L.; Velez, Federico G.
ABSTRACT: For patients with a complete, chronic abducens nerve palsy and resulting abduction deficit, a transposition procedure is often the procedure of choice. One such transposition procedure involves transposing the superior rectus (SR) and inferior rectus (IR) laterally without disinserting or splitting either muscle. While effective, this procedure – like many transposition procedures – carries with it the risk of induced torsional or vertical misalignment. Here, we describe an adjustable variation of the above transposition procedure, one which potentially would allow for post-operative correction of induced vertical or torsional deviations.